Paternal and maternal predictors of affective and cognitive involvement of three-year-old Chilean children in Chile (Predictores del involucramiento afectivo y cognitivo de padres y madres con sus hijas/os de tres años en Chile). Issue 2 (3rd April 2023) - Aldoney, Daniela; Prieto, Fernanda
ABSTRACT: Maternal and paternal involvement are an important predictor of child development. In the current study, we describe the cognitive and affective involvement of parents with their three-year-old children in a sample of 115 Chilean parents of medium/low socioeconomic status. Additionally, we analysed differences in the level of involvement of mothers and fathers and examined the relationship between depressive symptoms, parental stress, number of children, level of parental education, gender of the child and parental involvement. We performed a descriptive, correlational and regression analysis. The results revealed that mothers and fathers report higher levels of affective than cognitive involvement. When comparing mothers and fathers, mothers reported higher levels of cognitive and affective involvement. Paternal stress and depressive symptoms were negatively associated with cognitive and affective involvement with their children. In mothers, more children and stress were associated with lower levels of cognitive involvement with their children.